Peran Penting Sinematografi dalam Pendidikan pada Era Teknologi Informasi dan Komunikasi - Miyarso, Estu (Dinamika Pendidikan, 2011)
This paper  discusses  the  important role  of  cinematography  as  a discipline  of  applied  science.  Linkages  digital  cinematography  with  the development of  multimedia as  a form  of  information and  communication technologies. Also  describes the implementation of cinematography in the field of educational technology or learning today.   Key Words:  Cinematography in The Field of Educational, Information and Communication Technologies  Times